2015
DOI: 10.1159/000435839
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Sialic Acid Levels and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study

Abstract: Background: To assess the association between serum sialic acid (SA) levels and nonalcoholic fatty liver disease (NAFLD) in a Chinese population. Methods: A cross-sectional study was performed among 3,898 Chinese who took their annual health examination. Serum SA levels and other clinical and laboratory parameters were measured. Results: A total of 18.11% fulfilled the diagnostic criteria of NAFLD. NAFLD subjects with/without metabolic syndrome (MS) had significantly higher serum SA levels than those without N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Although the sialyation status of fibrinogen in patients with nonalcoholic fatty liver disease has to our knowledge never been assessed, it has been reported that free plasma sialic acid levels are increased in patients with diabetes 70 and patients with nonalcoholic fatty liver disease. 71 Interestingly, the permeability of plasma clots from patients with fatty liver disease-related cirrhosis was much lower compared with that of clots from patients with alcohol-induced cirrhosis of comparable severity. Part of this difference was explained by fibrinogen levels, which were much higher in patients with fatty liver disease-associated cirrhosis.…”
Section: The Special Case Of Nonalcoholic Fatty Liver Diseasementioning
confidence: 97%
“…Although the sialyation status of fibrinogen in patients with nonalcoholic fatty liver disease has to our knowledge never been assessed, it has been reported that free plasma sialic acid levels are increased in patients with diabetes 70 and patients with nonalcoholic fatty liver disease. 71 Interestingly, the permeability of plasma clots from patients with fatty liver disease-related cirrhosis was much lower compared with that of clots from patients with alcohol-induced cirrhosis of comparable severity. Part of this difference was explained by fibrinogen levels, which were much higher in patients with fatty liver disease-associated cirrhosis.…”
Section: The Special Case Of Nonalcoholic Fatty Liver Diseasementioning
confidence: 97%
“…Sialic acids in glycolipids or glycoproteins have diverse functions, including formation of a protective cell surface barrier, involvement in interactions of white blood cells with endothelial lining of blood vessels, recognition by pathogens and toxins and facilitation of cell migration by some cancers [ 216 ]. Circulating sialic acid levels have been positively associated with metabolic syndrome and with NAFLD [ 217 , 218 ]. Fucosylated glycans are also involved in a variety of physiological and pathological procedures, including cell adhesion and migration, angiogenesis, malignancy, tumor metastasis as well as immune cell development and regulation [ 219 ].…”
Section: Glycomicsmentioning
confidence: 99%
“…Serum SA levels have been reported to be elevated in patients with coronary artery disease (CAD), type 1 and type 2 diabetes mellitus (DM), obesity, nonalcoholic fatty liver disease, and chronic renal failure, including patients on dialysis . Moreover, serum SA concentrations have been found to correlate with atherosclerotic risk factors, including blood levels of LDL‐C, triglycerides (TG), HDL‐C, fibrinogen, lipoprotein (a) (Lp(a)), and uric acid, as well as with albuminuria and carotid intima media thickness (CIMT) .…”
Section: Introductionmentioning
confidence: 99%